Теорія, методи та засоби структуризації поліфункціональних даних у розподілених комп’ютерних системах - Возна, Наталія Ярославівна (My University, 2020)
Дисертаційна робота присвячена вирішенню актуальної наукової проблеми розвитку теорії, методології удосконалення структур поліфункціональних обчислювальних засобів, які є компонентами складних комп’ютерних систем. В Україні та світовому просторі практично відсутній узагальнений підхід до проблеми розробки теоретичних основ структурної організації поліфункціональних даних у розподілених комп’ютерних та кіберфізичних системах. У дисертаційній роботі закладено нові й розвинуто існуючі теоретичні та прикладні основи критеріїв оцінки та розрахунку структурної складності створюваних і використовуваних компонентів складних розподілених комп’ютерних та кіберфізичних систем, що дозволило покращити системні характеристики компонентів комп’ютеризованих систем та ефективність їх застосування в кіберфізичних системах за рахунок зменшення структурної, апаратної та часової складності. Розробка теоретичних засад та практична реалізація методів оцінки та вдосконалення теорії структурної складності поліфункціональних даних дозволяє оптимізувати системні характеристики відповідних структурних рішень апаратно-програмних засобів складних комп’ютеризованих систем. Розроблені та реалізовані у мікроелектронному виконанні структурні рішення функціональних компонентів складних РКС. The work presented in the thesis is devoted to solving an actual scientific problem of development of the theory and methodology and improvement of multifunctional computing devices structures, which are the components of complex computer systems. In Ukraine and in the global space, there is practically no generalized approach to the problem of the development of theoretical foundations, methodology, and methods of analysis and improvement of the structural organization of multifunctional data in complex distributed computer and cyber physical systems. As a result of carrying out theoretical, program-modeling and experimental research the following basic scientific results were obtained: for the first time functions and attributes of the concept of multifunctional data structuring were developed; the existing criteria were generalized and new criteria were developed for assessing the structural and information and structural complexity of multifunctional data; the theoretical foundations of the following methods were developed: the structuring of MD in different Number Systems; determining the entropy of a quasistationary object states according to probabilistic and correlation information measures; structured conversion of color image pixel codes in the Haar-Krestenson’s Number System; monitoring states of a quasi-stationary object on the basis of the characteristic functional of digital processing of technological process parameters; structural processing of harmonic signals and detection of disturbances in high-voltage power grids on the basis of integral-differential processing of signals. The method of synthesized formation of alphanumeric data was improved. The method of pixel protection by means of convolution with pseudorandom sequences was further developed. Structural solutions of elements and functional components of complex DCSs were developed and implemented in microelectronics: high-speed parallel multibasis ADC based on the use of para-phase comparators with advanced functionality and source codes in Rademacher’s and Haar-Krestenson’s Number Systems with a delay of 4 micro-clock signals; improved structures of single-bit half binary adders with single-phase and para-phase input and output signals; single-bit full adders with para-phase switched inputs and para-phase outputs with a delay of sums and transfers of 1 micro-clock signal; single-bit full binary adder based on 8 valves with inverted inputs and outputs and with a delay of 2 micro-clock signals; high-speed multibit adders with logic elements "Exclusive I" and advanced half single-bit adders with para-phase and direct inputs and outputs in their structure; multipliers in different Number Systems whose performance is in 1-2 orders higher than in the known multipliers of Brown, Dadda, etc. Flow multiplier with reduced structural complexity of input and output buses by 4n 2 times in comparison with the parallel multipliers and a device for determining probabilistic entropy with deep parallelization of computation were developed. Structures of data exchange protocols in lower level networks of cyber-physical systems were further developed. Synthesized small size keyboard providing cryptographic protection when exchanging data was improved. Диссертация посвящена решению актуальной научной проблемы развития теории, методологии совершенствования структур полифункциональных вычислительных средств, которые являются компонентами сложных компьютерных систем. В Украине и мировом пространстве практически отсутствует обобщенный подход к проблеме разработки теоретических основ структурной организации полифункциональных данных в распределенных компьютерных и киберфизичних системах. В диссертационной работе заложены новые и развиты существующие теоретические и прикладные основы критериев оценки и расчета структурной сложности создаваемых и используемых компонентов сложных распределенных компьютерных и киберфизичних систем, что позволило улучшить системные характеристики компонентов компьютеризированных систем и эффективность их применения в киберфизичних системах за счет уменьшение структурной, аппаратной и временной сложности. Разработка теоретических основ и практическая реализация методов оценки и совершенствования теории структурной сложности полифункциональных данных позволяет оптимизировать системные характеристики соответствующих структурных решений аппаратно-программных средств сложных компьютеризированных систем. Разработаны и реализованы в микроэлектронном выполнении структурные решения функциональных компонентов сложных РКС.
Theory, methods and tools of structuring multifunctional data in distributed computer systems
Теория, методы и средства структуризации полифункциональных данных в распределенных компьютерных системах
Keywords: структуризація; структуризовані поліфункціональні дані; критерії структурної складності; розподілені комп’ютерні системи; функціональна, структурна, інформаційна складність; structuring; structured multifunctional data; structural complexity criteria; distributed computer systems; functional, structural and information complexity; структурирование; структурированные полифункциональные данные; критерии структурной сложности; распределенные компьютерные системы; функциональная, структурная, информационная сложность; 681.325.36